Comparison of Phytoconstituents, Total Phenol Contents and Free Radical Scavenging Capacities between Four Arum Species from Jerusalem and Bethlehem - Nidal Jaradat, Murad Abualhasan (Tabriz University of Medical Sciences, 2016)
Background: Palestine is a rich land with wild edible plants which used from the ancient times as food and medicine. Arum is a valuable genus of medicinal plants which is used in the ethnic medicine for treatment of cancer or consumed as integrated food. This work aimed to evaluate and compare the phytoconstituents, total phenols contents and free radical scavenging potential for Arum dioscoridis, Arum elongatum, Arum hygrophilum and Arum palaestinum a members of Palestinian flora. Methods: Phytoconstituents screened by using standard analytical methods, total phenols determined by using Folin Ciocalteu's method and antioxidant activities were assessed by DPPH assay. Results: The crude extracts of Arum plant studied species revealed the presence of several biologically active phytochemicals with the highest quantity of saponin, alkaloid, phenols and flavonoids. For A. dioscoridis, A. elongatum, A. hygrophilum and A. palaestinum free radical scavenging activities were 6.7±0.75µg/ml, 19.9±0.63µg/ml, 9.9±0.49µg/ml, and 6.9±0.62µg/ml respectively, while the IC50 for Trolox was 4.8±0.39µg/ml as well as the total phenols contents for these species were 60.07 ±0.12, 27.49 ±0.32, 41.75±0.12 and 53.17±0.22 (mg GAE/g extract), ±SD respectively. Conclusion: The antioxidant activities in the studied Arum plant species showed a marked correlation with their total phenols contents. A. dioscoridis and A. palaestinum had the highest antioxidant activities with high contents of total phenols and they can be used as perfect choices for manufacturing of pharmaceutical, cosmeticeuticals and nutraceutical formulations.